Relation of Mild Traumatic Brain Injury history to abnormalities on a preliminary Neuroendocrine screen; A multicenter LIMBIC-CENC analysis. (16th April 2022) - Walker, William C.; Werner, Jk; Agyemang, Aa; Allen, Cm; Resch, Je; Troyanskaya, M; Kenney, K
ABSTRACT: Primary Objectives: Determine if an abnormal preliminary neuroendocrine disorder (NED) blood test screen is associated with mild TBI (mTBI) history or post-concussiveclinical features. Research Design: Observational Methods: Among 1, 520 participants with military combatexposure, we measured randomly timed serum levels of insulin-likegrowth factor-1, thyroid stimulating hormone (TSH), and total testosterone as a preliminary NED screen. Using multivariable models, we analyzed relation of screen results in mTBI group membership and post-concussiveclinical features (fatigue, depression, cognitive symptoms, executive function, processing speed). Results: None of the mTBI positive groups, including repetitive (≥3 mTBI) and blast-related, differed from the non-TBIcontrols on rates of abnormal lab screen or rates of growth hormone deficiency (GHD), hypothyroidism or male hypogonadism in treatment records. Lab screen findings were also not associated with any clinical feature. Conclusions: This study shows no evidence that remote mTBI(s) or implicated post-concussiveclinical features are linked to GHD, hypothyroidism or male hypogonadism. Large case-controlstudies incorporating more definitive neuroendocrine disorder NED testing (TSH plus thyroxine, early morning testosterone, LH, FSH, prolactin and GH provocative testing) are needed to determine whether mTBI(s) alone elevate one's risk for chronic NED and how best to select patients for comprehensive testing.